(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In recent years, due to improvement of internet web pages, documentary recorded video and audio data were presented for the audience over the world to use in the way of increasing knowledge in all spheres of life. Furthermore, in learning English for general purposes, learners prefer watching video documentaries to understand English language at all levels. The effective side of watching recorded visual aids is that it will be able to help enhance learners’ even basic knowledge at once. This paper highlights some thoughts and ideas about advantages of watching video for learners who study English at all levels. We conducted a research with 15 students from the faculty of Technical Engineering on the issues of comprehending video data and their attitudes to it.